Bespoken Nanoceria: An Effective Treatment in Experimental Hepatocellular Carcinoma. Issue 4 (14th October 2020) - Fernández‐Varo, Guillermo; Perramón, Meritxell; Carvajal, Silvia; Oró, Denise; Casals, Eudald; Boix, Loreto; Oller, Laura; Macías‐Muñoz, Laura; Marfà, Santi; Casals, Gregori; Morales‐Ruiz, Manuel; Casado, Pedro; et al.
Abstract : Background and Aims: Despite the availability of new‐generation drugs, hepatocellular carcinoma (HCC) is still the third most frequent cause of cancer‐related deaths worldwide. Cerium oxide nanoparticles (CeO2 NPs) have emerged as an antioxidant agent in experimental liver disease because of their antioxidant, anti‐inflammatory, and antisteatotic properties. In the present study, we aimed to elucidate the potential of CeO2 NPs as therapeutic agents in HCC. Approach and Results: HCC was induced in 110 Wistar rats by intraperitoneal administration of diethylnitrosamine for 16 weeks. Animals were treated with vehicle or CeO2 NPs at weeks 16 and 17. At the eighteenth week, nanoceria biodistribution was assessed by mass spectrometry (MS). The effect of CeO2 NPs on tumor progression and animal survival was investigated. Hepatic tissue MS‐based phosphoproteomics as well as analysis of principal lipid components were performed. The intracellular uptake of CeO2 NPs by human ex vivo perfused livers and human hepatocytes was analyzed. Nanoceria was mainly accumulated in the liver, where it reduced macrophage infiltration and inflammatory gene expression. Nanoceria treatment increased liver apoptotic activity, while proliferation was attenuated. Phosphoproteomic analysis revealed that CeO2 NPs affected the phosphorylation of proteins mainly related to cell adhesion and RNA splicing. CeO2 NPs decreased phosphatidylcholine‐derived arachidonic acid and reverted the HCC‐induced increase of linoleic acid in several lipid components. Furthermore, CeO2 NPs reduced serum alpha‐protein levels and improved the survival of HCC rats. Nanoceria uptake by ex vivo perfused human livers and in vitro human hepatocytes was also demonstrated. Conclusions: These data indicate that CeO2 NPs partially revert the cellular mechanisms involved in tumor progression and significantly increase survival in HCC rats, suggesting that they could be effective in patients with HCC.